Adoption of climate-smart agriculture technology in drought-prone area of India – implications on farmers' livelihoods - Pal, Barun Deb; Kapoor, Shreya; Saroj, Sunil; Jat, Mangi Lal; Kumar, Yogesh; Anantha, KH (Emerald Publishing Limited, 2022)
Laser land leveling (LLL) is a climate-smart technology that improves water use efficiency and reduces risk in crop cultivation due to weather variability. Hence, this technology is useful for cultivating water-intensive crops in a sustainable way. Given this background, the state government of Karnataka initiated to promote LLL in drought-prone districts and selected Raichur district for implementation. Moreover, farmers in this district had observed drought situation during monsoon paddy growing season in 2018. Therefore, this study attempts to investigate the importance of LLL technology for paddy cultivation under drought conditions.